2010
DOI: 10.1007/s00464-009-0837-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic common bile duct exploration and holmium laser lithotripsy: a novel approach to the management of common bile duct stones

Abstract: Laparoscopic CBD exploration via a transcystic approach together with holmium laser lithotripsy is a safe and effective way to clear large solitary or impacted CBD stones. This technique also avoids choledochotomy and may be used in concert with other methods such as ERCP, percutaneous cholangioscopy, and open exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…Consequently, the majority of surgeons use the transductal approach directly through the CBD. Regardless of exact technique used, the high rates of duct clearance reported with LBDE119 120 125–129 can be increased to near 100% with the availability of intraductal piezoelectric or LL 130. Long-term results also appear favourable 131 132.…”
Section: Surgical Management Of Cbdsmentioning
confidence: 99%
“…Consequently, the majority of surgeons use the transductal approach directly through the CBD. Regardless of exact technique used, the high rates of duct clearance reported with LBDE119 120 125–129 can be increased to near 100% with the availability of intraductal piezoelectric or LL 130. Long-term results also appear favourable 131 132.…”
Section: Surgical Management Of Cbdsmentioning
confidence: 99%
“…Of these, basket retrieval systems may increase the risk of bile duct mucosa injury . EHL is an inexpensive technique used mainly for difficult biliary stones; however, there are many complications, such as recurrent jaundice, cholangitis, perforation and bleeding .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies demonstrated that holmium laser lithotripsy was a safe and effective method to manage impacted biliary stones; however, it required continuous visual control of the fragmentation procedure because of the high energies with long pulse durations that are used; the probe contacting the bile duct wall may result in perforation, bleeding, biliary leakage and other serious complications . Moreover, because of the inability of the surgeon to visualize the area, holmium laser lithotripsy should be ceased in severe intraoperative haemobilia, which is extremely hard to manage .…”
Section: Discussionmentioning
confidence: 99%
“…1214 Reports have described the combined use of a choledochoscope with lithotripsy in treating calculi of the bile duct. 15,16 The dual-band, dual-pulse laser lithotripsy developed in the 1990s has replaced the holmium laser as the optimal laser lithotripsy method. Moreover, this method is more suitable for use in treating biliary calculi.…”
Section: Discussionmentioning
confidence: 99%